Nilai Pendidikan Karakter dalam Tradisi Halal Bihalal - Azzahro, Fatimah; Salamah, Hartini; Fasha, Julia (TSAQOFAH, 2025)
This study aims to explore the values of character education within the tradition of halal bi halal using a qualitative approach. The method employed is a literature review, analysing various sources related to the concept of character education and the halal bihalal tradition. As an analytical framework, this research uses Thomas Lickona’s concept of character education, which includes moral knowledge, moral feelings, and moral actions. The findings indicate that halal bihalal embodies strong moral values, such as tolerance, honesty, integrity, respect, and courtesy. This tradition also strengthens aspects of moral feelings, such as conscience awareness, self-respect, empathy, self-control, and humility, which encourage individuals to act in accordance with the moral values they have learned. Furthermore, halal bihalal fosters moral actions through practices of mutual cooperation and social solidarity, reflecting the importance of collaboration and togetherness in community life. Thus, the halal bihalal tradition is not merely an occasion for social gathering but also serves as an effective medium for character education, contributing to the development of a harmonious and cultured society. Therefore, efforts are needed to preserve and reinforce the character education values within this tradition to ensure its relevance in the modern era.